Attitude performance and institutional talk in criminal interrogation - Barrett, Elena (2019)
This study examines police membership categorization in addition to investigator attitudes as they are constructed and performed within the process of interrogation (Benneworth, 2009; Stokoe, 2009, 2010). The data for this study consists of one, two-hour long interrogation between two sex crimes investigators (I1 and I2) and a fellow police officer and suspect of sexual assault (S). The ensuing interaction was analysed using conversation analysis, through the lens of discursive psychology (Potter, 1998; Potter & Edwards, 1999).The study looks at I1 and I2’s attitudes as they are constructed and performed through discourse, (Potter, 1998; Wiggins & Potter, 2003) and at what this attitude performance seeks to achieve within the interrogation. Furthermore, it examines the way in which I1 and I2 utilize membership categorization through police-specific institutional talk. Finally, the study will demonstrate how these interactional elements align with certain components of the Reid Technique, an interrogative process used widely by police in North America (Ofshe & Leo, 1997; King & Snook, 2018).